PUPUK HAYATI (BIOFERTILIZER) ALTERNANTIF SUBTITUSI PENGGUNAAN PUPUK KIMIAWI - asrul asrul asrul (Partner, 2019)
Increased population growth implies the intensive management of agricultural land for food fulfillment. As a result, the use of chemical fertilizers among farmers continues to increase to support this intensive agriculture. UREA, NPK and Super Phosphate Fertilizers are chemical fertilizers that are used by farmers to meet the macro nutrients of plants, especially N, P and K. The problem is that excessive and intensive use of chemical fertilizers turns out to have a negative impact on both agricultural land and accumulated residues in plants which are then consumed by humans. One of the efforts to substitute chemical fertilizers in agricultural land by applying biofertilzer or biofertilzer. Biofertilizers are fertilizers that use the services of microorganisms (bacteria) to meet plant nutrient needs.